Komparasi Standar Akuntansi Keuangan SAK ETAP dan SAK EP dalam Penyusunan Laporan Keuangan Koperasi - Eka Setiajatnika; Udin Hidayat (J-Coop : Journal of Co-operative, 2025)
This study aims to examine the differences between the implementation of the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) and the Financial Accounting Standards for Private Entities (SAK EP) in the preparation of financial statements for Savings and Loan Cooperatives (KSP) in West Java, as well as to evaluate the cooperatives’ readiness for transitioning to the new standard. Employing a comparative descriptive design with a mixed-methods approach, data were collected through in-depth interviews with cooperative management, internal accountants, and auditors, alongside document analysis of financial statements and applicable accounting standards. The findings reveal that the implementation of SAK ETAP still encounters significant challenges, particularly regarding limited human resources and underdeveloped accounting information systems, which compromise the quality of financial reporting. Meanwhile, readiness to adopt SAK EP remains low, due to its greater complexity and demand for enhanced technical competence. Nonetheless, the adoption of SAK EP is anticipated to improve the relevance, reliability, and transparency of cooperative financial reports. Therefore, strong support from the government and the Indonesian Institute of Accountants (IAI)—through training, dissemination, and technical assistance—is deemed essential. The study recommends strengthening human capital, improving information systems, and ensuring continuous external support to facilitate a successful transition to SAK EP. These findings are expected to serve as a reference for policymakers and cooperative practitioners aiming to enhance financial reporting quality in the cooperative sector.